2021
DOI: 10.1371/journal.pone.0256186
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of uranyl (UO2)2+ with bidentate ligands: XRD, spectroscopic, computational, and biological studies

Abstract: Three new uranyl complexes [(UO2)(OAc)2(CMZ)], [(UO2)(OAc)2(MP)] and [(UO2)(OAc)2(SCZ)] were synthesized and characterized by elemental analysis, FT-IR, UV-Vis spectroscopy, powder XRD analysis, and molar conductivity. The IR analysis confirmed binding to the metal ion by the sulfur and ethoxy oxygen atoms in the carbimazole (CMZ) ligand, while in the 6-mercaptopurine (MP) ligand, the sulfur and the N7 nitrogen atom of a purine coordinated binding to the metal ion. The third ligand showed a 1:1 molar ratio and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The obtained values for the HOMO and LUMO for the metal complexes and the free organic molecules have been used to calculate the energy gap, E g = E LUMO − E HOMO . This indicator is usually used to assess the reactivity of the molecules [33]. A small E g value indicates the reactivity of the complexes through to the softness character, while the large energy gap between HOMO and LUMO complicates the transition of the electron, and we can express this as hard compounds.…”
Section: Frontier Molecular Orbitals (Fmos) Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained values for the HOMO and LUMO for the metal complexes and the free organic molecules have been used to calculate the energy gap, E g = E LUMO − E HOMO . This indicator is usually used to assess the reactivity of the molecules [33]. A small E g value indicates the reactivity of the complexes through to the softness character, while the large energy gap between HOMO and LUMO complicates the transition of the electron, and we can express this as hard compounds.…”
Section: Frontier Molecular Orbitals (Fmos) Parametersmentioning
confidence: 99%
“…Table 4 shows that the E g values were decreased after coordination to the metal ion, and CTNZ had the smallest value among the investigated compounds and was thus the most reactive molecule. For more details of the molecules' properties, we estimated the global reactivity descriptors, which are absolute electronegativities (χ), absolute hardness (η), chemical potentials (µ), global softness (S), and global electrophilicity (ω), using equations in our previous work [33] and illustrated in Table 4. The absolute softness is the reverse of the absolute hardness, which describes the sense to react with other molecules such as biological compounds, and we could arrange them according to the absolute softness (S) as follows: VO-CTNZ > VO-MNZ > VO-PNZ.…”
Section: Frontier Molecular Orbitals (Fmos) Parametersmentioning
confidence: 99%
“…The output files were visualized by Gauss View software and showed that the optimized geometries did not have an imaginary frequency, which confirmed that the structures were on the potential energy surface. Moreover, the HOMO and LUMO energies and orbital levels were extracted using Gauss View to calculate the following essential quantum parameters: energy gap (E gap = E LUMO − E HOMO ), absolute electronegativities (χ = −E HOMO +E LUMO /2), absolute hardness (ɳ = E LUMO − E HOMO /2), chemical potentials (μ = -χ), global softness (S = 1/2ɳ), and global electrophilicity (ω = π2/2ɳ) [18] .…”
Section: Methodsmentioning
confidence: 99%
“…The experiments employed a constant compound concentration and gradually increasing (1.57–5.15 μM) of Ct-DNA concentrations. The Ct-DNA was dissolved in a buffer solution (pH 7.4) and confirmed to be free of protein using the UV absorbance ratio (A 260 /A 280 ), which was in the range 1.8-1.9 [18] , [19] . The effective binding constants (K b ) were evaluated using the Benesi-Hildebrand equation …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation